2005
DOI: 10.1515/bc.2005.066
|View full text |Cite
|
Sign up to set email alerts
|

Kunitz-type Bauhinia bauhinioides inhibitors devoid of disulfide bridges: isolation of the cDNAs, heterologous expression and structural studies

Abstract: Bauhinia bauhinoides cruzipain inhibitor (BbCI) and Bauhinia bauhinioides kallikrein inhibitor (BbKI) are cysteine and serine proteinase inhibitors structurally homologous to plant Kunitz-type inhibitors, but are devoid of disulfide bridges. Based on cDNA sequences, we found that BbKI and BbCI are initially synthesized as a prepropeptide comprising an N-terminal signal peptide (19 residues), the mature protein (164 residues) and a C-terminal targeting peptide (10 residues). Partial cDNAs encoding the mature en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 35 publications
3
55
1
2
Order By: Relevance
“…Individual values of each isoform were very close to this average. This confirms classification of these isoforms as bII class proteins (Sreerama and Woody, 2003), as these results are in agreement with the structural characteristics of other plant Kunitz-type inhibitors described in the literature (Araújo et al, 2005;Haq and Khan, 2003). In addition, static fluorescence spectra of the three isoforms measured after excitation at 280 and 295 nm, gave the same k max emission value at 341 nm; this value corresponds to the position of spectra of class II chromophores, in which tryptophan residues are exposed to the surface of the compact native protein molecule (Burstein et al, 1973).…”
Section: Structural Characterizationsupporting
confidence: 91%
“…Individual values of each isoform were very close to this average. This confirms classification of these isoforms as bII class proteins (Sreerama and Woody, 2003), as these results are in agreement with the structural characteristics of other plant Kunitz-type inhibitors described in the literature (Araújo et al, 2005;Haq and Khan, 2003). In addition, static fluorescence spectra of the three isoforms measured after excitation at 280 and 295 nm, gave the same k max emission value at 341 nm; this value corresponds to the position of spectra of class II chromophores, in which tryptophan residues are exposed to the surface of the compact native protein molecule (Burstein et al, 1973).…”
Section: Structural Characterizationsupporting
confidence: 91%
“…By contrast, TI3 and TI5 inhibited both trypsin and chymotrypsin with similar efficiency. TI6 was the only elastase inhibitor, a rare activity among plant KTIs (Valueva et al, 2000;Araujo et al, 2005;Sumikawa et al, 2006). These functional differences presumably reflect the sequence diversity of the KTI family.…”
Section: Biochemical Analysis Indicates Functional Diversification Ofmentioning
confidence: 99%
“…The reactive site is located on a protruding reactive loop, which forms H-bonds with the active groove of the protease. Most KTI proteins have four conserved Cys residues that form two disulfide bridges, although examples with only one or no disulfide bridges are known (do Socorro et al, 2002;Araujo et al, 2005;Macedo et al, 2007). Evidence from several studies suggests that the first disulfide bridge, which surrounds the reactive loop, is necessary for the inhibitory activity of most KTIs (DiBella and Liener, 1969;do Socorro et al, 2002).…”
mentioning
confidence: 99%
“…Interestingly, we found that EcTI efficiently inhibited the formation of both 66-kDa and 64-kDa MMP-2 under PMA/plasminogen-stimulating conditions, whereas aprotinin could only block transformation into 64-kDa MMP-2 but, similar to aprotinin EcTI, decreases the plasminogen-induced proMMP-9 activation approving direct inhibition of plasmin by the plant inhibitor. By contrast, neither the plant-derived elastase/cysteine proteinase inhibitor BbCI nor the kallikrein inhibitor BbKI Araujo et al, 2005) Bereitgestellt von | Universitaetsbibliothek der LMU Muenchen Angemeldet | 129.187.254.47 Heruntergeladen am | 19.12.13 12:38 showed any effect on the proMMP-2 and -9 activation, indicating that the respective target serine proteinases do not interact with the MMP system in our cell model.…”
Section: Discussionmentioning
confidence: 66%